ANALISIS KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS VIII RADEN SALEH SMP NEGERI MODEL TERPADU MADANI PALU PADA SISTEM PERSAMAAN LINEAR DUA VARIABEL - Nurul Esra Apriliani; I Nyoman Murdiana; Anggraini Anggraini; Gandung Sugita (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to obtain a description of the ability to understand the mathematical concepts of 8th grade students of Raden Saleh SMP Negeri Madani Palu Integrated Model on the material of the Two-Variable Linear Equation System. This type of research is descriptive qualitative. The subjects in this study consisted of 2 people, where 1 student with high math ability, and 1 student with low math ability. Data collection techniques are using tests and interviews.  Data analysis uses 3 stages, namely, data reduction, data exposure, and conclusion drawing. The results showed that (1) Analysis of concept understanding of high mathematics ability subjects on the indicator of restating a concept, able to explain the meaning of the system of linear equations of two variables using their own language but, incomplete; on the indicator of classifying objects according to certain properties in accordance with the concept, able to classify examples and not examples of SPLDV; on the indicator of using and utilizing and selecting certain procedures or operations in solving problems, able to solve problems using existing procedures. (2) Analysis of concept understanding of low mathematics ability subjects on the indicator of restating a concept, able to restate a concept of a system of linear equations of two variables by looking at answers on the internet; on the indicator of classifying objects according to certain properties in accordance with the concept, not yet able to classify examples and not examples of SPLDV; on the indicator of utilizing and selecting certain procedures or operations, unable to solve the problem given.